Physical and cultural determinants of postpartum pelvic floor support and symptoms following vaginal delivery: a protocol for a mixed-methods prospective cohort study. Issue 1 (10th January 2017) - Nygaard, Ingrid E; Clark, Erin; Clark, Lauren; Egger, Marlene J; Hitchcock, Robert; Hsu, Yvonne; Norton, Peggy; Sanchez-Birkhead, Ana; Shaw, Janet; Sheng, Xiaoming; Varner, Michael
Abstract : Introduction: Pelvic floor disorders (PFDs), including pelvic organ prolapse (POP), stress and urgency urinary incontinence, and faecal incontinence, are common and arise from loss of pelvic support. Although severe disease often does not occur until women become older, pregnancy and childbirth are major risk factors for PFDs, especially POP. We understand little about modifiable factors that impact pelvic floor function recovery after vaginal birth. This National Institutes of Health (NIH)-funded Program Project, 'Bridging physical and cultural determinants of postpartum pelvic floor support and symptoms following vaginal delivery', uses mixed-methods research to study the influences of intra-abdominal pressure, physical activity, body habitus and muscle fitness on pelvic floor support and symptoms as well as the cultural context in which women experience those changes. Methods and analysis: Using quantitative methods, we will evaluate whether pelvic floor support and symptoms 1 year after the first vaginal delivery are affected by biologically plausible factors that may impact muscle, nerve and connective tissue healing during recovery (first 8 weeks postpartum) and strengthening (remainder of the first postpartum year). Using qualitative methods, we will examine cultural aspects of perceptions, explanations of changes in pelvic floor support, and actions taken by Mexican-American and Euro-American primipara, emphasising early changes after childbirth. We will summarise project results in a resource toolkit that will enhance opportunities for dialogue between women, their families and providers, and across lay and medical discourses. We anticipate enrolling up to 1530 nulliparous women into the prospective cohort study during the third trimester, following those who deliver vaginally 1 year postpartum. Participants will be drawn from this cohort to meet the project's aims. Ethics and dissemination: The University of Utah and Intermountain Healthcare Institutional Review Boards approved this study. Data are stored in a secure password-protected database. Papers summarising the primary results and ancillary analyses will be published in peer-reviewed journals.